2020
DOI: 10.1080/12298093.2020.1850172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Genetic Diversity of Agaricus bisporus Accessions through Phylogenetic Analysis Using Single-Nucleotide Polymorphism (SNP) Markers

Abstract: Agaricus bisporus , commonly known as the button mushroom, is widely cultivated throughout the world. To breed new strains with more desirable traits and improved adaptability, diverse germplasm, including wild accessions, is a valuable genetic resource. To better understand the genetic diversity available in A. bisporus and identify previously unknown diversity within accessions, a phylogenetic analysis of 360 Agaricus spp. accessions using single-nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Genetic diversity analysis of cultivars and wild strains is underway to aid the development of new A. bisporus cultivars with desirable traits and improved adaptability. Diversity of A. bisporus resources, cultivars, and wild strains was assessed using molecular RFLP, SSR, and SNP markers [30,32,[46][47][48]. Genetic diversity was also assessed using SSR markers to incorporate disease resistance into breeding programs [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity analysis of cultivars and wild strains is underway to aid the development of new A. bisporus cultivars with desirable traits and improved adaptability. Diversity of A. bisporus resources, cultivars, and wild strains was assessed using molecular RFLP, SSR, and SNP markers [30,32,[46][47][48]. Genetic diversity was also assessed using SSR markers to incorporate disease resistance into breeding programs [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some molecular markers and quantitative trait loci (QTL) for important agronomic traits were characterized for a substantial collection of A. bisporus strains over the last decade [34][35][36][37]. Most of them are related with disease resistance and yield, including bruising (discoloration after damaging the cap skin), earliness (first day picking), firmness, cap color, compost colonization, and scaling of mushroom caps [34,35].…”
Section: Its Sequencing Of a Bisporus Strainsmentioning
confidence: 99%
“…Most of them are related with disease resistance and yield, including bruising (discoloration after damaging the cap skin), earliness (first day picking), firmness, cap color, compost colonization, and scaling of mushroom caps [34,35]. In addition to these data, a recent report evaluated the genetic diversity of 170 accessions of A. bisporus by analyzing 111 single-nucleotide polymorphism (SNP) markers [37] based on the previously published KASP (Kompetitive Allele-Specific PCR) markers [36]. Together, these results represent valuable genetic resources that are potentially useful for breeding, enabling the development of strains with superior agronomic traits.…”
Section: Its Sequencing Of a Bisporus Strainsmentioning
confidence: 99%
“…The whole-genome resequencing of 29 strains revealed that the Tibetan Plateau population was significantly differentiated from the European and American populations [ 33 ]. The commercial cultivars of A. bisporus have been studied used nuclear SSR and SNP markers, and the results showed they belonged to two groups [ 34 , 35 ]. However, the patterns of intraspecific evolution and population genetic history of A. bisporus remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%